Agomelatine's antiglycoxidative action—In vitro and in silico research and systematic literature review - Nesterowicz, Miłosz; Lauko, Kamil Klaudiusz; Żendzian-Piotrowska, Małgorzata; Ładny, Jerzy Robert; Zalewska, Anna; Maciejczyk, Mateusz (Frontiers in Psychiatry, 2023)
Agomelatine is an atypical antidepressant drug enhancing norepinephrine and dopamine liberation; nevertheless, additional mechanisms are considered for the drug’s pharmacological action. Since protein glycoxidation plays a crucial role in depression pathogenesis, agomelatine's impact on carbonyl/oxidative stress was the research purpose. Reactive oxygen species scavenging (hydroxyl radical, hydrogen peroxide, nitrogen oxide) and antioxidant capacity (2,2-diphenyl-1-picrylhydrazyl radical and ferrous ion chelating assays) of agomelatine were marked. Agomelatine’s antiglycoxidation properties were assayed in sugars- (glucose, fructose, galactose) and aldehydes- (glyoxal, methylglyoxal) glycated bovine serum albumin (BSA). Aminoguanidine and α-lipoic acid were used as standard glycation/oxidation inhibitors. Agomelatine did not show meaningful scavenging/antioxidant capacity versus standards. Sugars/aldehydes increased glycation (↑kynurenine, ↑N-formylkynurenine, ↑dityrosine, ↑advanced glycation end products, ↑β-amyloid) and oxidation (↑protein carbonyls, ↑advanced oxidation protein products) parameters besides BSA. Standards restored BSA baselines of glycation and oxidation markers, unlike agomelatine which sometimes even intensifies glycation above BSA+glycators levels. Molecular docking analysis of agomelatine-in-BSA demonstrated its very low affinity could proclaim non-specific bonding and glycation factors attachment simplifying. Thereby the drug may stimulate brain adaptation to carbonyl/oxidative stress as the systematic review indicates. Moreover, the drug’s active metabolites could exert an antiglycoxidative effect.